A Benthic Monitor for Coastal Water Dissolved Oxygen Variation: Mn/Ca Ratios in Tests of an Epifaunal Foraminifer. Issue 12 (27th December 2021) - Guo, Xiaoyi; Wei, Qinsheng; Xu, Bochao; Burnett, William C.; Bernhard, Joan M.; Nan, Haiming; Lian, Ergang; Yang, Shouye; Yu, Zhigang
Abstract: An appropriate proxy could help to better understand dissolved oxygen variations in the past, helping to predict potential outcomes of future environmental changes. In the Changjiang Estuary (China), the foraminifer Cribrononion subincertum ( C. subincertum ) shows a distinct population maximum in the topmost sediment, an indication of an epifaunal species. Therefore, the geochemical composition of C. subincertum tests could record changes in the region's bottom water chemistry. Our results showed that Mn/Ca ratios in tests of living (Rose‐Bengal stained) C. subincertum analyzed by LA‐ICP‐MS were responsive to variations of bottom water dissolved oxygen concentrations, with average foraminiferal Mn/Ca ratios three times higher during low‐oxygen period than in winter. In the uppermost centimeters of sediment, wider ranges of foraminiferal Mn/Ca occurred in summer compared to winter ranges. Our results imply that this epifaunal benthic foraminiferal species could serve as a useful benthic monitor with the Mn/Ca ratios representing a reliable proxy of hypoxia in the past. Plain Language Summary: We explored how different dissolved oxygen contents impacts the geochemical composition of benthic foraminiferal shells (tests) in a dynamic coastal setting. We collected sediment samples and identified living (Rose Bengal stained) foraminifera from the Changjiang (Yangtze) Estuary, one of the largest seasonally hypoxic (low oxygen) zones in the world. Sampling at 1‐cm intervals revealed Cribrononion subincertum predominantly inhabits the surface sediments in this area. Mn/Ca ratios in living tests of this benthic foraminifer were measured via laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS). As expected, Mn/Ca ratios responded to changing Mn in the bottom waters which itself is correlated to DO levels. Our results imply that this epifaunal benthic foraminiferal species could serve as a useful benthic monitor with the Mn/Ca ratios representing a reliable proxy of hypoxia in the past. Key Points: The microhabitat of Cribrononion subincertum was found to be epifaunal in the Changjiang Estuary Cribrononion subincertum Mn/Ca ratios were responsive to variations of bottom water dissolved oxygen Epifaunal benthic foraminifera can be a robust monitor for coastal hypoxia; more species need to be similarly studied